Penggunaan Media Bangun Ruang untuk Meningkatkan Pemahaman Konsep pada Siswa Sekolah Dasar - Rizqi Tri Ruhmana; Vivi Rulviana; Raras Setyo Retno (Universitas PGRI Madiun, 2024)
This is where the teacher's role is really needed in providing guidance for students who have difficulty learning in mathematics subjects, especially for spatial construction material in class II of SDN Duren 04 by carrying out innovations, one of which is using learning media to make it easier for students to receive lesson material and increase understanding of concepts. build space for class II students. Based on the results of the research and data analysis that has been carried out, it can be concluded that the optimal use of spatial structure learning media in mathematics learning can increase understanding of the concept of spatial structure in class II students at SDN Duren 04. This can be proven from observation data and result data The tests in cycle II experienced an increase from the previous cycle. In cycle I, observation data was obtained with a percentage of 62.5%, while in cycle II eleven it was 79.2%. For test result data in cycle I, the percentage was 53%, while in cycle II the percentage was 86.7%. Based on these data, it can be concluded that the use of spatial learning media in class II building material can increase students' understanding of concepts as evidenced by an increase in learning outcomes and student activities in class.